Determinação da atividade enzimática e antioxidante de variedades comerciais de Ananas Comosus e avaliação do efeito de tratamento térmico e do uso de aditivos químicos - Costa, Aline Silva (2011)
The pineapple is a tropical fruit orchard in the country most cultivated and its fruit is eaten raw, or in the form of ice cream, candy, popsicles, juices processed, fruit in syrup and so on. However, few varieties are used in industry for lack of knowledge of their biochemical characteristics, among them the pectinolytic enzymes activity and oxidative that are among those that decrease the shelf life of products made from fruits. Moreover, despite the growing concern regarding the antioxidant activity in fruit products, little is known about the effect of processing on this activity, especially in derivatives of pineapple. Therefore, the objective of the study to determine the activity of enzymes polygalacturonase (PG), pectin methylesterase (PME), polyphenol oxidase (PPO) and peroxidase (PER), and ways to inactivate them by the addition of chemical inhibitors (ascorbic acid, metabisulfite sodium and calcium chloride) and physical (temperature and time of treatment) of commercial varieties of Ananas comosus. Furthermore, studied the total phenolic content and antioxidant activity in the pineapple and possible amendment of this activity after the treatments applied to enzymatic inactivation. To obtain maximum enzyme activity was made an experimental design by analyzing the pH and NaCl concentration on enzymatic extraction method. The results showed that the highest activities obtained in this experiment were: 1.0 M NaCl, pH 6.0 for PER (4752.9 U / g), pH < 4.6 for PPO (81.6 U / g)1.0 M NaCl for PME (5.8 U / g) and 2.0 M NaCl for PG (0,000034 U/g.h-1) . Using these parameters was determined the enzymatic activity of varieties Imperial, Vitoria, and Perola acquired from two different places. Observed higher activities of pectic enzymes in Variety Imperial and Victoria, but these varieties showed lower activity of oxidative enzymes characteristic most advantageous to the food industry, because the PER is the most thermoresistant enzyme (inactivation difficult). We used the central composite design and response surface methodology to study the effect of time (1-9 min), temperature (27 to 86 ° C) and concentration of the chemical inhibitor (0 to 200 mg / L of sodium metabisulphite, ascorbic acid and calcium chloride) in the inactivation of the PER and PPO. Sodium metabisulphite was found to be the best inhibitor for PER, 100% could inactivate this enzyme at a concentration of 130 mg / L at a temperature of 78 ° C for 3 min damage from high doses of the inhibitor and high temperatures on fruit . For PPO treatment with ascorbic acid was given at 190 mg / L for 3 min at 75 ° C, although this treatment was not effective to inactivate the enzyme 100% PER. These treatments had a positive effect on the amount of total phenolics and antioxidant activity, possibly because these treatments inactivate enzymes that degrade the phenolic compounds (PPO and PER), and observed a moderate to high correlation between the total phenols and antioxidant activity.